Tingkat Perkembangan Biologi Nematoda Puru Akar (Meloidogyne spp.) pada Berbagai Jenis Tanaman Famili Solanaceae - NANDRIATI, PUTU AYU FRAHMI; SUDANA, I MADE; SUDARMA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.1, Januari 2020, 2020)
Level Developmental Biology Root Nematode (Meloidogyne spp.) On Different Types of Plants Family Solanaceae Meloidogyne spp. is an important parasitic nematodes which attack many crops in Indonesia. One of the host plants that are favored by Meloidogyne spp. is family solanaceae. Solanaceace plant widely cultivated in Indonesia because of high economic value and become an important food ingredient. Attacks Meloidogyne spp. makes losing a very high yield so that the necessity of controlling performed to suppress the attack of Meloidogyne spp .. Control with nematicides is a fast and practical way, but the impact on the environment to be unfavorable. Therefore, controlling use of technical culture by means of crop rotation using a crop that is less favored by Meloidogyne spp. be an environmentally friendly alternative to control. This research see the development of larval stages II to IV and adult nematodes at 1 gram root and larval stage II at 300 grams of soil by using red pepper plant (Capsicum annuum L.), cayenne pepper (Capsicum frutecesns L.), eggplant (Solanum melongena L .) and tomato plants (Lycopersicum esculentum Mill).